BZT305- Vertebrate Zoology (Zoologi Vertebrata) - PPSKJ, Pusat Pengajian Sains Kajihayat (Universiti Sains Malaysia, 2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 BZT305- Vertebrate Zoology (Zoologi Vertebrata) Duration : 2 hours (Masa : 2 jam)